Least squares method of relative errors for parameter estimation of systems under non-classical assumptions - Слабоспицький, Олександр (Київський національний університет імені Тараса Шевченка, 2025)
The problem of optimal estimation of regression model parameters based on available observations of the dependent variable and all regressors is considered. It is suggested to use the least squares method of relative residuals to solve this problem. The estimate of this method is the point at which the sum of squares of relative residuals of the regression model reaches its minimum, not the sum of squares of absolute residuals of the model, as in the ordinary least squares method, which can be called the least squares method of absolute residuals. The value of the quality functional of the considered method no longer depends on the units of measurement of the available observations. In the paper, the explicit form of the representation of the optimal estimate of the least squares method of relative errors in a situation where the classical assumption is valid, which guarantees its uniqueness, is extended to the case when this assumption is violated and the estimate is no longer unique. In the latter situation, there is a need to use the Moore-Penrose matrix pseudo-inversion operator. Corresponding explicit expressions for the estimation error by this method are also presented for both cases. In addition, as a consequence, for the weighted least squares method, in the case of using an arbitrary positive definite matrix as the weight matrix, for both of the above-mentioned situations, explicit forms of representation of the corresponding optimal estimate of this method and the expression for the estimation error are also given by analogy. Pages of the article in the issue: 197 - 201 Language of the article: Ukrainian

Розглянуто задачу оптимального оцінювання параметрів регресійної моделі по доступним спостереженням залежної змінної та усіх регресорів. Пропонується для розв’язання цієї проблеми використовувати метод найменших квадратів відносних похибок. Оцінка цього методу — це точка у якій досягає свого мінімуму сума квадратів відносних  похибок регресійної моделі, а не сума квадратів абсолютних  похибок моделі, як у звичайному методі найменших квадратів, який можна назвати методом найменших квадратів абсолютних похибок. Значення функціонала якості розглянутого методу вже не залежить від одиниць виміру доступних спостережень. У роботі явна форма представлення оптимальної оцінки методу найменших квадратів відносних похибок у ситуації, коли справедливо класичне припущення, яке гарантує її єдиність, поширена на випадок, коли це припущення порушено  і оцінка вже не є єдиною. У останній ситуації виникає потреба у  використанні оператора псевдообернення матриць за Муром – Пенроузом. Також для обох випадків представлені відповідні явні вирази для похибки оцінювання цим методом. Крім цього, в якості наслідку, для зваженого методу найменших квадратів, у випадку використання як вагової матриці довільної позитивно визначеної матриці, для обох вищезгаданих ситуацій по аналогії також наведено явні форми представлення відповідної оптимальної оцінки цього методу та виразу для похибки оцінювання.
Метод найменших квадратів відносних похибок для оцінювання параметрів систем за некласичних припущень
Keywords: regression model; parameter estimation; non-classical assumption; Moore – Penrose pseudo-inversion operator; least squares method; weighted least squares method; least squares method of relative errors; регресійна модель; оцінювання параметрів; некласичні припущення; оператор псевдообернення за Муром – Пенроузом; метод найменших квадратів; зважений метод найменших квадратів; метод найменших квадратів відносних залишків.